Phylogenetic-based nomenclatural proposals for Ophiocordycipitaceae (Hypocreales) with new combinations in Tolypocladium (2014)
ABSTRACT: Ophiocordycipitaceae is a diverse family comprising ecologically, economically, medicinally, and culturally important fungi. The family was recognized due to the polyphyly of the genus Cordyceps and the broad diversity of the mostly arthropod-pathogenic lineages of Hypocreales. The other two cordyceps-like families, Cordycipitaceae and Clavicipitaceae, will be revised taxonomically elsewhere. Historically, many species were placed in Cordyceps, but other genera have been described in this family as well, including several based on anamorphic features. Currently there are 24 generic names in use across both asexual and sexual life stages for species of Ophiocordycipitaceae. To reflect changes in Art. 59 in the International Code of Nomenclature for algae, fungi, and plants (ICN), we propose to protect and to suppress names within Ophiocordycipitaceae, and to present taxonomic revisions in the genus Tolypocladium, based on rigorous and extensively sampled molecular phylogenetic analyses. When approaching this task, we considered the principles of priority, monophyly, minimizing taxonomic revisions, and the practical utility of these fungi within the wider biological research community.